Pengembangan Desain Kemasan Produk Bumbu Pecel KWT Kenanga, Ngestiharjo, Daerah Istimewa Yogyakarta - Kalifatullah Ermaya, Sir; Nur Laela Ermaya, Husnah; Muchran, dkk, Murniady (E-Coops-Day, 2024)
We carried out this Community Service Activity (PKM) for the Women Farmers Group (KWT) "Kenanga", situated in Ngestiharjo, Special Region of Yogyakarta. This activity aims to provide insight into the packaging of its flagship product, namely pecel seasoning. We use guidance on appropriate packaging to enhance the product's competitiveness. This PKM activity was successfully implemented. In addition, the activity provides participants with motivation, fostering persistence and enthusiasm for product development. We then apply the designed packaging and labels to the product, aiming to boost sales volume and establish a product with a significant competitive edge